Concepts and Design Thinking Innovation Addressing the Global Financial Needs The INFINTECH Way Foundations Part I - Serrano, Martín (NowOpen, 2023)
In this first part of the INFINITECH book series, which is a series of three books, the principles of the modern economy that make the modern financial sector and FinTech the most disruptive areas in today's global economy are discussed. INFINITECH envision many opportunities emerging for activating new channels of innovation on the local and global scale while at the same time catapulting opportunities for more disruptive user-centric services. At the same time, INFINITECH is the result of a shared vision from a representative global group of experts, providing a common vision and identifying impacts in the financial and insurance sectors.